Prevention of transgenerational transmission of disease susceptibility through perinatal intervention - Takahiro Nemoto; Norimasa Sagawa (Endocrine Journal)
The observational findings of Barker’s original epidemiological studies were generalized as the Barker hypothesis and extended as the Developmental Origins of Health and Disease (DOHaD) theory. Barker et al. proposed that low birthweight (LBW) was associated with the occurrence of various noncommunicable diseases (NCDs) later in life. In other words, LBW itself is associated with the development of NCDs. This led to the DOHaD theory which proposed that an organism may have a specific period of developmental plasticity that is highly sensitive to the factors in its environment, and that combinations of acquired constitution and environmental factors may adversely affect health and risk the formation of NCDs. Due to undernutrition during the fetal period, the fetus acquires an energy-saving constitution called a thrifty phenotype due to adaptations of the metabolic and endocrine systems. It has been suggested that stimuli experienced early in development can persist throughout life and induce permanent physiological changes that predispose to NCDs. It has since become clear that the adverse environmental effects during the prenatal period are also intergenerationally and transgenerationally inherited, affecting the next generation. It has been shown that nutritional interventions such as methyl-donner and epigenome editing can restore some of the impaired functions and reduce the risk of developing some diseases in the next generation. This review thus outlines the mechanisms underlying various disease risk formations and their genetic programs for the next generation, which are being elucidated through studies based on our fetal undernutrition rat models.